Estudo comparativo das complicações terapêuticas no Lúpus Eritematoso Sistêmico e nas glomerulopatias idiopáticas. - Balbi, André Luis [UNESP]; Barbosa, R. A.; Lima, M. C.; Almeida, D. B. (Elsevier, 2001)
PURPOSE: To evaluate the therapeutic complications due to the use of immunosupressors in patients with nephropathy. METHODS: 76 patients who had used steroids and cyclophosphamide were retrospectively studied. The cases were divided into three groups: G1= 15 patients with Systemic Lupus Erythematosus without renal lesion; G2= 33 patients with lupus nephritis and G3= 28 patients with nephrotic syndrome owing to idiopathic glomerulopathy. RESULTS: There were no differences related to time of follow up (G1= 42.4 +/- 51, G2= 52.3 +/- 51, G3= 41.8 +/- 47.8 months), total used dosage of steroids (G1= 20, G2= 28, G3= 16 grams) and time of drug use (G1= 20, G2= 26, G3= 14.5 months). About cyclophosphamide use, there was no difference in the percentage of patients who used it (13% in G1, 51% in G2, 28% in G3), but the patients from G1 received lower total dosage than those from G2 (p<0.05). Cushingoid appearance, epigastric distress, psychiatric disorders, diabetes mellitus and ocular alterations occurred in all the three groups, with no statistically significant differences. The infections complications, those considered more severe clinically, were more frequent in G2 (G1= 6%, G2= 15%, G3= 0% - p<0.05), the same occurring with the deaths (7% in G1, 30% in G2, 0% in G3 - p<0.05). CONCLUSION: In patients with lupus nephritis there were more infections complications owing to prolonged immunosuppresion what may indicate a severity marker of this type of lesion.
A comparative study of therapeutic complications in Systemic Lupus Erythematosus and in idiopathic glomerulopathy
Keywords: corticosteroid; cyclophosphamide; immunosuppressive agent; methylprednisolone; prednisone; adult; comparative study; female; follow up; human; lupus erythematosus nephritis; male; nephrotic syndrome; retrospective study; systemic lupus erythematosus; Adrenal Cortex Hormones; Adult; Cyclophosphamide; Female; Follow-Up Studies; Humans; Immunosuppressive Agents; Lupus Erythematosus, Systemic; Lupus Nephritis; Male; Methylprednisolone; Nephrotic Syndrome; Prednisone; Retrospective Studies